Gestão em cadeias criativas: a escrita do Projeto Político-Pedagógico e a produção da cultura de colaboração - Carvalho, Giselle Maria Magnossão Vilar de (2015)
This work has as its general objective the critical investigation of school management practices via the study of the activity network proposed for the composition of the Politico-Pedagogical Project of a private school in São Paulo. This piece of research sought to critically understand if and how the management of the activities and the organization of the argumentation made it possible for this network to become a Creative Chain for the production of shared meanings between the participants in a Collaborative Culture. The theoretical outline of this work is based on the Theory of Socio-Historico-Cultural Activity, considering Vygotsky's (1926, 1927, 1930, 1934), Leontiev's (1977, 1978), and Engeström's (1987, 1999a, 1999b, 1999c) discussions. Founded upon the Critical Collaborative Research (MAGALHÃES, 2007a, 2007b, 2009), this research chose as corpus the discursive interactions between the participants of the activities of the writing of the Politico-Pedagogical Project, which were produced and collected for analysis via audio recordings, and the texts of the initial and final documents of the school's Politico-Pedagogical Project. The data have been analysed from a dialogico-enunciative perspective, with support from Bakhtin's Circle's (1929-30, 1934-35) studies. Categories organized based on the three levels of language analysis were used: a) on the enunciative level, categories founded in Bronckart (999/2007) were used; b) on the discursive level, the argumentative structure (LIBERALI, 2009), the interactive sequences (ORSOLINI, 2005), and the types of arguments (PERELMAN & OBRECHTS-TYTECA, 1958/2005) were analyzed; and c) on the linguistic level, the argumentative operators (KOCH, 1992/2004), the modalizations (BRONCKART, 1999), the conversational and valuation mechanisms (LIBERALI, 2013), and the person, time, and place deictics (SANTOS, 2010) were analyzed. The mapping of externalized senses and meanings in the documents and activities and the analysis of the discursive interactions allowed the identification of advances and the intertwining of voices, both within a given activity and among activities, as well as the evolution of lexical choices in the final document, with the predominance of the lexicon linked to the socio-historico-cultural perspective. The management of the activities and the organization of the argumentation, however, sometimes conducted to oscillations in the presence of colaboration and in the production of shared meanings, which interfered in the constitution of the Creative Chain.This work has allowed the deepening of the theoretical discussion about the concept of management in the socio-historico-cultural frame, as well as pointed to possibilities of school management practices based on this perspective, signaling, especially, the importance of manager formation for the acting in this theoretical frame